Making Global Value Chains Work for Development - Taglioni, Daria (Washington, DC: World Bank, 2016)
Economic, technological, and political shifts as well as changing business strategies have driven firms to unbundle production processes and disperse them across countries. Thanks to these changes, developing countries can now increase their participation in global value chains (GVCs) and thus become more competitive in agriculture, manufacturing and services. This is a paradigm shift from the 20th century when countries had to build the entire supply chain domestically to become competitive internationally. For policymakers, the focus is on boosting domestic value added and improving access to resources and technology while advancing development goals.